2004
DOI: 10.1111/j.1524-4725.2004.30116.x
|View full text |Cite
|
Sign up to set email alerts
|

Topical Imiquimod Treatment for Nodular Basal Cell Carcinomas: An Open-Label Series

Abstract: Imiquimod 5% cream may be another treatment modality for nodular BCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 10 publications
3
34
0
1
Order By: Relevance
“…In this study, a local recurrence of BCC was not observed clinically within the 3-year follow-up period. The rates of clearance and recurrence in these patients are in accordance with those reported in previous studies that focused on other tumour locations [3,4]. In another study, 5% imiquimod was applied to the eyelids with good results in terms of clearance, but the authors state that the excellent recurrence rate was tentative because of the short-term follow-up time [5].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In this study, a local recurrence of BCC was not observed clinically within the 3-year follow-up period. The rates of clearance and recurrence in these patients are in accordance with those reported in previous studies that focused on other tumour locations [3,4]. In another study, 5% imiquimod was applied to the eyelids with good results in terms of clearance, but the authors state that the excellent recurrence rate was tentative because of the short-term follow-up time [5].…”
Section: Discussionsupporting
confidence: 86%
“…Recent studies recommend the expansion of its use as an effective non-surgical treatment of nodular BCC [3].…”
Section: Introductionmentioning
confidence: 99%
“…Imiquimod probably stimulates a cell-mediated immunity, which is naturally suppressed by BCC, and can clear the tumor [5,6]. Nevertheless, there are five histopathological types of BCC: nodular, superficial, micronodular, morpheaform, and sclerosing, of which superficial and nodular BCCs are considered nonaggressive forms [7]. Nodular BCC is the most common tumor type in the region of the eyelids (78%) [8].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported to have clinical efficacy in the management of both superficial3 4 and nodular basal cell carcinomas (BCCs) 5 6…”
Section: Introductionmentioning
confidence: 99%